(untitled) - Akunin, Boris (New York, 2004)
On 15th March 1878 Lord Littleby, an English eccentric and collector, is found murdered in his Paris house together with nine members of his staff. A gold whale in the victim's hand leads Erast Fandorin to board the Leviathan, the world's largest steamship, as the murderer is one of the 142 First Class passengers. Commissioner Gauche of the French police has narrowed down the suspects to ten, and they are forced to eat together at every meal time in the ship's Windsor Suite until 'the Crime of the Century' is solved. But is the murderer really sat around the table, and can Erast Fandorin discover his or her identity before Gauche? As more passengers are murdered and Leviathan heads towards Calcutta, Fandorin needs all his investigative skills to find the truth. Boris Akunin's latest tape-turner again transports the reader back to the late nineteenth-century. In Leviathan he pays homage to Agatha Christie with a cast of characters and plot which grips you from the first page.
Keywords: Russian literature,Văn học Nga